Parents' Understanding of the Balanced Nutrition Guidelines by Indonesia's Ministry of Health: A Case Study at Almaarif Kindergarten - Indi Diana; Sandy Tegariyani Putri Santoso (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
The problem of malnutrition in children remains a controversial topic of discussion and an unresolved challenge, especially concerning parental knowledge. Parents must be knowledgeable about balanced nutrition before proceeding to the implementation stage. The purpose of this study was to determine the extent of parental knowledge about the 2014 Balanced Nutrition Guidelines that were developed by the Ministry of Health in Indonesia. In order to collect data, the questionnaire was distributed to 80 respondents who were parents of students at Al-Maarif Singosari Kindergarten in Malang Regency. The questionnaire focused on evaluating parents' understanding of the recommendations for a balanced diet. The research findings revealed that 64% of parents demonstrated a strong comprehension of the balanced diet recommendations, while 36% exhibited a moderate understanding. However, these results are insufficient to ensure the effective implementation of balanced nutrition in children unless the knowledge is consistently translated into practice. Further research is needed on the relationship between parents' understanding of balanced nutrition and children's nutritional levels.